'Red Sun in the Blue Sky': Rohith Vemula's Utopian Republic. (September 2016) - Sukumar, N.
Rohit Vemula's institutional murder triggered a national debate on the constitutional values, that is, Equality, Justice and Freedom, enshrined in the Ambedkarite Constitution. After their suspension from the university spaces—classroom, hostel, campus life—Rohith and his friends walked out of the hostel, clutching their meagre possessions, a mattress, some books and a huge portrait of Ambedkar clearly demonstrating their source of strength and confidence to fight the casteist and communal mindsets. The message was loud and clear. It was a call for arms to all Ambedkarites to rebel and rally against an undemocratic social system. However, for Rohith, it was not simply a battle against entrenched privileges but also an opportunity to fashion an alternative universe, as he very poignantly expressed 'The Red Sun in the Blue Sky'. This perspective is an attempt to unravel Rohith's dreams and aspirations which have found echoes across university campuses.